VD_FINDINFO Décision / 2025 / 645 vom 22. August 2025 - VD Tribunal cantonal (2025)
REJET DE LA DEMANDE, PROFIL D'ADN, ACTE D'ORDRE SEXUEL AVEC UN ENFANT | 29 al. 2 Cst., 197 al. 1 CPP (CH), 255 al. 1bis CPP (CH), 257 CPP (CH)